EVALUATION OF IN VIVO IMMUNOMODULATORY ACTIVITY OF AQUEOUS AND ETHANOLIC EXTRACT OF EULOPHIA NUDA L. - Kanase, Vanita; T Patil, Diptesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to evaluate the in vivo immunomodulatory activity of an aqueous and ethanolic extract of dried tubers of Eulophia nuda (ENA and ENE). Methods: Effect of both the extracts was evaluated on delayed-type hypersensitivity (DTH) response, serum antibody response, and cyclophosphamide-induced myelosuppression in Swiss albino mice. Results: The extracts showed stimulation of DTH reaction in mice in response to T-cell dependent antigen by both ENE () and ENA (); significant increase in serum antibody titer at of ENA (768.01) and ENE (768.33) extract at 200 mg/kg, compared to control group (213.33); Combined treatment of ENA+Cytochromes P450 [CYP]-25 mg/kg and ENE+CYP-25mg/kg (50, 100, and 200 mg/kg) doses of ENA and ENE each with 25 mg/kg resulted in restoration of bone marrow activity as compared with CYP treatment alone. Conclusion: Both specific and non-specific immunostimulating properties of the ENE and ENA tubers in in vivo experimental methods suggest its therapeutic usefulness in immunocompromised conditions.